Handbook of image and video processing - Bovik, Alan C. (Alan Conrad), 1958- (Amsterdam ; Boston, MA : Elsevier Academic Press, 2005)
55% new material in the latest edition of this must-have for students and practitioners of image & video processing! This Handbook is intended to serve as the basic reference point on image and video processing, in the field, in the research laboratory, and in the classroom. Each chapter has been written by carefully selected, distinguished experts specializing in that topic and carefully reviewed by the Editor, Al Bovik, ensuring that the greatest depth of understanding be communicated to the reader. Coverage includes introductory, intermediate and advanced topics and as such, this book serves equally well as classroom textbook as reference resource. Provides practicing engineers and students with a highly accessible resource for learning and using image/video processing theory and algorithms Includes a new chapter on image processing education, which should prove invaluable for those developing or modifying their curricula Covers the various image and video processing standards that exist and are emerging, driving todays explosive industry Offers an understanding of what images are, how they are modeled, and gives an introduction to how they are perceived Introduces the necessary, practical background to allow engineering students to acquire and process their own digital image or video data Culminates with a diverse set of applications chapters, covered in sufficient depth to serve as extensible models to the readers own potential applications About the Editor Al Bovik is the Cullen Trust for Higher Education Endowed Professor at The University of Texas at Austin, where he is the Director of the Laboratory for Image and Video Engineering (LIVE). He has published over 400 technical articles in the general area of image and video processing and holds two U.S. patents. Dr. Bovik was Distinguished Lecturer of the IEEE Signal Processing Society (2000), received the IEEE Signal Processing Society Meritorious Service Award (1998), the IEEE Third Millennium Medal (2000), and twice was a two-time Honorable Mention winner of the international Pattern Recognition Society Award. He is a Fellow of the IEEE, was Editor-in-Chief, of the IEEE Transactions on Image Processing (1996-2002), has served on and continues to serve on many other professional boards and panels, and was the Founding General Chairman of the IEEE International Conference on Image Processing which was held in Austin, Texas in 1994. * No other resource for image and video processing contains the same breadth of up-to-date coverage * Each chapter written by one or several of the top experts working in that area * Includes all essential mathematics, techniques, and algorithms for every type of image and video processing used by electrical engineers, computer scientists, internet developers, bioengineers, and scientists in various, image-intensive disciplines.
Introduction to digital image and video processing / Alan C. Bovik -- Basic gray-level image processing / Alan C. Bovik -- Basic binary image processing / Alan C. Bovik -- Basic tools for image Fourier analysis / Alan C. Bovik -- Image processing education / Umesh Rajashekar, Alan C. Bovik, Daniel Sage, Michael Unser, Lina J. Karam and Reginald L. Lagendijk -- Basic linear filtering with application to image enhancement / Alan C. Bovik and Scott T. Acton -- Nonlinear filtering for image analysis and enhancement / Gonzalo R. Arce, Jan Bacca and Josβe L. Paredes -- Morphological filtering for image enhancement and feature Detection / Petros Maragos -- Wavelet denoising for image enhancement / Dong Wei, Umesh Rajashekar and Alan C. Bovik -- Basic methods for image restoration and identification / Reginald L. Lagendijk and Jan Biemond -- Regularization in image restoration and reconstruction / W. Clem Karl -- Multichannel image recovery / Nikolas P. Galatsanos, Miles N. Wernick, Aggelos K. Katsaggelos and Rafael Molina -- Multi-frame image restoration / Timothy J. Schulz -- Iterative image restoration / Aggelos K. Katsaggelos and Chun-Jen Tsai -- Motion detection and estimation / Janusz Konrad -- Video enhancement and restoration / Reginald L. Lagendijk, Peter M.B. van Roosmalen, Jan Biemond, Andrei Rareπs and Marcel J.T. Reinders -- Local and global stereo methods / Yang Liu and J.K. Aggarwal -- Image sequence stabilization, mosaicking, and superresolution / Rama Chellappa, S. Srinivasan, G. Aggarwal and A. Veeraraghavan -- Computational models of early human vision / Lawrence K. Cormack -- Multiscale image decompositions and wavelets / Pierre Moulin -- Random field models / P. Fieguth and J. Zhang -- AM-FM image models : fundamental techniques and emerging trends / Joseph P. Havlicek, Peter C. Tay and Alan C. Bovik -- Image noise models / Charles Boncelet -- Color and multispectral image representation and display / H.J. Trussell -- Statistical modeling of photographic images / Eero P. Simoncelli -- Statistical methods for image segmentation / Sridhar Lakshmanan -- Multiband techniques for texture classification and segmentation / B.S. Manjunath, G.M. Haley, Wei-Ying Ma and S.D. Newsam -- Video segmentation / A. Murat Tekalp -- 2D and 3D motion tracking in digital video / Georgios Stamou, Michail Krinidis, Evangelos Loutas, Nikos Nikolaidis and Ioannis Pitas -- Adaptive and neural methods for image segmentation / Joydeep Ghosh -- Gradient and Laplacian edge detection / Phillip A. Mlsna and Jeffrey J. Rodriguez -- Diffusion partial differential equations for edge detection / Scott T. Acton -- Shape smoothing and PDEs / Frβedβeric Guichard, Lionel Moisan and Jean-Michel Morel -- PDEs for morphological scale spaces and eikonal applications / Petros Maragos -- Geometric active contours for image segmentation / Vicent Caselles, Ron Kimmel and Guillermo Sapiro -- Software for image and video processing / K. Clint Slatton and Brian L. Evans -- Lossless coding / Lina J. Karam -- Block truncation coding (BTC) / Paul Salama, Martha Saenz and Edward J. Delp -- Fundamentals of vector quantization / Mohammad A.U. Khan and Mark J.T. Smith -- Wavelet image compression / Zixiang Xiong and Kannan Ramchandran -- Lossy image compression : JPEG and JPEG2000 standards / Rashid Ansari, Christine Guillemot and Nasir Memon -- The JPEG lossless image compression standards / Nasir Memon, Christine Guillemot and Rashid Ansari -- Multispectral image coding / Daniel Tretter, Nasir Memon and Charles A. Bouman -- Recovery methods for postprocessing of compressed images / Y. Yang, N.P. Galatsanos and A.K. Katsaggelos -- Basic concepts and techniques of video coding and the H.261 standard / Barry Barnett -- Interframe subband/wavelet scalable video coding / John W. Woods, Peisong Chen, Yongjun Wu and Shih-Ta Hsiang -- Digital video transcoding / Shizhong Liu and Alan C. Bovik -- MPEG-1 and MPEG-2 video standards / Supavadee Aramvith and Ming-Ting Sun -- MPEG-4, H.264/AVC, and MPEG-7 : new standards for the digital video industry / Berna Erol, Adriana Dumitraπs, Faouzi Kossentini, Anthony Joch and Gary Sullivan -- Embedded video codecs / Minhua Zhou and Raj Talluri -- Image scanning, sampling, and interpolation / Jan P. Allebach -- Video sampling and interpolation / Eric Dubois -- Image quantization, halftoning, and printing / Ping Wah Wong -- Perceptual criteria for image quality evaluation / Thrasyvoulos N. Pappas, Robert J. Safranek and Junqing Chen -- Structural approaches to image quality assessment / Zhou Wang, Alan C. Bovik and Eero P. Simoncelli -- Information theoretic approaches to image quality assessment / Hamid R. Sheikh and Alan C. Bovik -- Image and video indexing and retrieval / Michael A. Smith and Tsuhan Chen -- A unified framework for video summarization, browsing, and retrieval / Ziyou Xiong, Yong Rui, Regunathan Radhakrishnan, Ajay Divakaran and Thomas S. Huang -- Video communication networks / Dan Schonfeld -- Joint source-channel coding for video communications / Fan Zhai, Yiftach Eisenberg and Aggelos K. Katsaggelos -- Watermarking techniques for image authentication and copyright protection / Anastasios Tefas, Nikos Nikolaidis and Ioannis Pitas -- Visual cryptography : the combinatorial and halftoning frameworks / Gonzalo R. Arce, Giovanni Di Crescenzo and Zhi Zhou -- Synthetic aperture radar algorithms / Ron Goodman and Walter Carrara -- Computed tomography / R.M. Leahy and R. Clackdoyle -- Cardiac image processing / Joseph M. Reinhardt and William E. Higgins -- Computer-aided detection and diagnosis in mammography / Mehul P. Sampat, Mia K. Markey and Alan C. Bovik -- Fingerprint classification and matching / Anil Jain and Sharath Pankanti -- Face recognition from still images and videos / Shaohua Kevin Zhou and Rama Chellappa -- How iris recognition works / John Daugman -- Exploiting visual information in automatic speech processing / Petar S. Aleksic, Gerasimos Potamianos and Aggelos K. Katsaggelos -- Confocal microscopy / Fatima A. Merchant, Keith A. Bartels, Alan C. Bovik and Kenneth R. Diller -- Computer-assisted microscopy / Fatima A. Merchant and Kenneth R. Castleman -- Statistical models of targets and clutter for use in bayesian object recognition / Anuj Srivastava, Michael I. Miller and Ulf Grenander.
Includes bibliographical references and index.
Keywords: Image processing -- Digital techniques -- Handbooks, manuals, etc; Video compression -- Handbooks, manuals, etc; Video; Electronic books; Handbooks, manuals, etc